Reproductive Potential of the Mackerel Scad, Decapterus macarellus (Cuvier, 1833) in the Coastal Waters of Tanzania - Sululu, Joseph S; Lugendo, Blandina R; Benno, Benaiah L (Tanzania Journal of Science, 2022)
This study investigated the reproductive biology of Decapterus macarellus locally known as ''Msumari", one of the most economically important scad fish along the coastline of Tanzania. Fish samples were collected from ring net artisanal fishers operating in Tanga and Bagamoyo coastal waters, monthly between April 2019 and September 2020. Findings indicated that D. macarellus spawns throughout the year with peaks in August at Tanga and September at Bagamoyo. Overall sex ratios (M: F) were 1:1.03 (Tanga) and 1:1.2 (Bagamoyo) in favour of females. The males and females of D. macarellus at Tanga attained the first maturity at 145.5 mm and 153.2 mm, respectively, whereas at Bagamoyo males attained first maturity at 149.9 mm and females at 156.9 mm. Batch fecundity was not statistically significant (U = 500.5; p = 0.73), with Tanga having mean values (± SE) of 46,105.9 ± 4243.4 ova and Bagamoyo 43,082 ± 2272.9 ova. Although this species appears to spawn all year round, management interventions such as seasonal closure and reduced fishing effort should be used during their spawning peaks to protect the spawners, recruits and ensure the species' long-term survival in the Tanzanian coastal waters. Keywords: Scad; Decapterus macarellus; reproductive potential; ring net fishery; Tanzania.